Sarcomas Harboring EWSR1::PATZ1 Fusions: A Clinicopathologic Study of 17 Cases - Dehner, Carina A; Torres-Mora, Jorge; Gupta, Sounak; Kipp, Benjamin R; Halling, Kevin C; Chen, Shaoxiong; Warmke, Laura M; Michal, Michael; Alani, Ali; Yu, Wendong; Kovacs, Krisztian; Obeidin, Farres; et al. (Modern pathology, 2024)
Soft tissue sarcomas harboring EWSR1::PATZ1 are a recently recognized entity with variable morphology and a heterogeneous immunohistochemical profile. We studied 17 such tumors. The tumors occurred in 12 men and 5 women (median age, 50 years; range, 15-71 years), involved the thoracoabdominal soft tissues (14 cases; 82%), lower extremities (2 cases; 12%), and tongue (1 case; 6%), and ranged from 0.7 to 11.3 cm (median, 4.7 cm). All but 1 patient received complete surgical resection; 7 were also treated with neoadjuvant chemo/radiotherapy. All cases showed typical features of EWSR1::PATZ1 sarcoma, including uniform round to spindled cells, fibromyxoid matrix, fibrous bands, hyalinized vessels, and pseudoalveolar/microcystic spaces. Unusual features, seen in a subset of cases, included degenerative-appearing nuclear atypia, epithelioid cytomorphology, mature fat, abundant rhabdomyoblasts, high mitotic activity, and foci with increased cellularity and nuclear atypia. Positive immunohistochemical results were desmin (16/17, 94%), MyoD1 (13/14, 93%), myogenin (6/14, 43%), GFAP (10/10, 100%), S100 protein (15/17, 88%), SOX10 (7/13, 54%), keratin (10/17, 59%), CD99 (4/11, 36%), H3K27me3 (retained expression 9/9, 100%), p16 (absent expression 1/4, 25%), and p53 (wild type 3/3, 100%). Fusion events included EWSR1 exon 8::PATZ1 exon 1 (14/17, 82%), EWSR1 exon 9::PATZ1 exon 1 (2/17, 12%), and EWSR1 exon 7::PATZ1 exon 1 (1/17, 6%). No evaluated tumor had alterations of CDKN2A/B and/or TP53, or MDM2 amplification. Clinical follow-up (16 patients: median, 13.5 months; range, 1-77 months) showed distant metastases in 3 patients (1/3 at time of presentation) and no local recurrences. At the time of last follow-up, 14 patients were disease free, 1 was alive with disease, 1 was dead of disease (at 13 months), and 1 had an indeterminant pulmonary nodule. We conclude that the morphologic spectrum of EWSR1::PATZ1 is broader than has been previously appreciated. Although more long-term follow-up is needed, the prognosis of these very rare sarcomas may be more favorable than previously reported.
Keywords: Soft Tissue Neoplasms; Sarcoma; Female; Repressor Proteins; transkripční faktory; represorové proteiny; ženské pohlaví; transkripční faktory Krüppel-like; S100 Proteins; lidé; Transcription Factors; prognóza; sarkom; Male; nádorové biomarkery; protein EWS vázající RNA; Prognosis; proteiny S100; lidé středního věku; Biomarkers, Tumor; nádory měkkých tkání; mužské pohlaví; Middle Aged; RNA-Binding Protein EWS; Kruppel-Like Transcription Factors; Humans